2011 IEEE International Conference on Robotics and Automation 2011
DOI: 10.1109/icra.2011.5980366
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of grasp type and frequency in daily household and machine shop tasks

Abstract: This paper presents a study on the usage frequency of different grasp types throughout the daily functions of a professional house maid and a machinist. Subjects wore a head-mounted camera that recorded their hand usage during their daily work activities. This video was then analyzed, recording grasp type and associated time stamps, as well as information related to the task and object. The results show that nearly 80% of the time the house maid used just six grasps and the machinist used nine. This data, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 7 publications
0
78
0
Order By: Relevance
“…According to Zheng et al, between 2,500 and 3,000 grasping motions of the unaffected dominant hand may be performed over an 8 h period during the work day [44]. A prosthetic device will typically undergo 120 grasping motions per day [5].…”
Section: Durability/cycles Of Usementioning
confidence: 99%
“…According to Zheng et al, between 2,500 and 3,000 grasping motions of the unaffected dominant hand may be performed over an 8 h period during the work day [44]. A prosthetic device will typically undergo 120 grasping motions per day [5].…”
Section: Durability/cycles Of Usementioning
confidence: 99%
“…This taxonomy is not comprehensive, as it omits a number of common grasp types, for example gripping a pen or pencil, however this is still the most extensive and widely used taxonomy. It was initially informed by observation of activities of daily living, and then used to classify grip types in further studies such as those carried out by Lee et al [4] and Zheng et al [5]. Examination of the different grip studies showed that the most common grip types were the "Medium Wrap" and "Thumb-Index Finger" (see Figure 1 for detail of these) and the digits most often implemented in studies were the index finger and thumb.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the grip movement can be divided into two types those are power and precision grip. Then based on the object that interacts, grip movement can be divided into six types of movement those are cylindrical, tip, hook, palmar, spherical Anggriyawan Putranto, Ilham Priadythama, Susy Susmartini, and Pringgo W. Laksono Conceptual Design of 3 Independent Motor Actuation Transmission Systems for Low-Cost Anthropomorphic Prosthetic Hand and lateral [6]. In cylindrical/spherical, all fingers and metacarpal grasping around a cylindrical/spherical object such as a bottle/tennis ball.…”
Section: A Type Of Graspmentioning
confidence: 99%